2022
DOI: 10.3390/cancers14174067
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Mutations in Colorectal Liver Metastases: Prognostic Implications and Potential Therapeutic Strategies

Abstract: Surgery combined with chemotherapy and precision medicine is the only potential treatment for patients with colorectal cancer liver metastases (CRLM). The use of modern molecular biotechnology to identify suitable biomarkers is of great significance for predicting prognosis and formulating individualized treatment plans for these patients. BRAF mutations, particularly V600E, are widely believed to be associated with poor prognosis in patients with metastatic CRC (mCRC). However, it is unclear which specific fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…53 BRAF mutations are associated with poor prognosis in patients with metastatic CRC, with mortality rates nearly three times that of BRAF wild-type patients. 52 Schirripa et al reported that the median RFS and OS after resection of CRLM in BRAF-mutated patients were only 5.7 and 22.6 months, far lower than the figures of 14.4 and 63.3 months in wild-type patients. 54 A meta-analysis of six studies incorporating 1,857 patients revealed that patients with BRAF-mutated CRLM undergoing hepatectomy had significantly worse OS (HR 2.80, 95% CI: 2.09-3.77) and DFS (HR 2.29, 95% CI: 2.41-3.71) compared with BRAF wild-type patients.…”
Section: Brafmentioning
confidence: 91%
See 4 more Smart Citations
“…53 BRAF mutations are associated with poor prognosis in patients with metastatic CRC, with mortality rates nearly three times that of BRAF wild-type patients. 52 Schirripa et al reported that the median RFS and OS after resection of CRLM in BRAF-mutated patients were only 5.7 and 22.6 months, far lower than the figures of 14.4 and 63.3 months in wild-type patients. 54 A meta-analysis of six studies incorporating 1,857 patients revealed that patients with BRAF-mutated CRLM undergoing hepatectomy had significantly worse OS (HR 2.80, 95% CI: 2.09-3.77) and DFS (HR 2.29, 95% CI: 2.41-3.71) compared with BRAF wild-type patients.…”
Section: Brafmentioning
confidence: 91%
“…52 However, BRAF mutation was present in only 1 to 6.1% of resectable CRLM patients, which may be due to the rapid tumor growth and metastasis caused by mutations in BRAF gene. 52 Patients with BRAF-mutated metastatic CRC are more likely to develop peritoneal metastases, rarely present disease confined to the liver. 53 BRAF mutations are associated with poor prognosis in patients with metastatic CRC, with mortality rates nearly three times that of BRAF wild-type patients.…”
Section: Brafmentioning
confidence: 99%
See 3 more Smart Citations